Wild-type and pathogenic forms of ubiquilin 2 differentially modulate components of the autophagy-lysosome pathways - Akiko Idera; Lisa M. Sharkey; Yuki Kurauchi; Keiichi Kadoyama; Henry L. Paulson; Hiroshi Katsuki; Takahiro Seki (Journal of Pharmacological Sciences, 2023)
Missense mutations of ubiquilin 2 (UBQLN2) have been identified to cause X-linked amyotrophic lateral sclerosis (ALS). Proteasome-mediated protein degradation is reported to be impaired by ALS-associated mutations of UBQLN2. However, it remains unknown how these mutations affect autophagy-lysosome protein degradation, which consists of macroautophagy (MA), microautophagy (mA), and chaperone-mediated autophagy (CMA). Using a CMA/mA fluorescence reporter we found that overexpression of wild-type UBQLN2 impairs CMA. Conversely, knockdown of endogenous UBQLN2 increases CMA activity, suggesting that normally UBQLN2 negatively regulates CMA. ALS-associated mutant forms of UBQLN2 exacerbate this impairment of CMA. Using cells stably transfected with wild-type or ALS-associated mutant UBQLN2, we further determined that wild-type UBQLN2 increased the ratio of LAMP2A (a CMA-related protein) to LAMP1 (a lysosomal protein). This could represent a compensatory reaction to the impairment of CMA by wild-type UBQLN2. However, ALS-associated mutant UBQLN2 failed to show this compensation, exacerbating the impairment of CMA by mutant UBQLN2. We further demonstrated that ALS-associated mutant forms of UBQLN2 also impair MA, but wild-type UBQLN2 does not. These results support the view that ALS-associated mutant forms of UBQLN2 impair both CMA and MA which may contribute to the neurodegeneration observed in patients with UBQLN2-mediated ALS.